Developing future leaders, responsibilities of parents and the society - U Tun Aung, Maulana Akbar Shah (University Muslim Students Myammar, 2020)
Challenges of the youths in our society have been immensely increasing as they witness abundance of mischief, lawlessness, misconduct, cynicism, and criminal acts including cheating, deceitful behaviour, fraudulent acts, drug trafficking, drug abuse, alcoholic crimes, illegal gambling, brawls, fracas, skirmishes, vandalism, intolerance towards inter-religious societies and discrimination among races, etc. These disgraceful crimes and misconducts are being simultaneously generated in our communities because they have an absence of moralities and ethical values. In facts, These vlaue could only be overwhelmed by good parents and administrators, and people who are morally healthy and responsible for the welfare of the communities. Such phenomenon shapes the behaviour and attitude of the children painfully. In facts, all these wrongdoings begin from a house-whole, and they continue to spread to neighbourhoods and societies. Parents are critical figures in a house, and if they fail to shape their children, they will derail from their successful path. On the other hand, some of the social institutions, which are supposed to nurture good future leaders, have developed into the centers for immorality and the responsibility for these establishments which demonstrates depravity and disagreeable acts towards the youth. Under all these circumstances, it is an obligation for all good citizens of our society to suggest the best solution on how these problems can be tackled and solved appropriately. Finally, all these processes for the development of youth are foundations for shaping the future leader of a nation. This paper highlights the nature of childhood, nurturing the children, the process of developing good youth, the responsibilities of parents, children, and the members of the society. In reality, the elders know their duties, but most of the time, forget them for so many reasons. The author believes this research will bring the best solutions to assisting in shaping future leaders. Keywords: Youth, parents, society, leader, discipline, morality, responsibility.